Development and first validation of a patient-reported experience measure in chronic obstructive pulmonary disease (PREM-C9). Issue 6 (26th April 2019) - Hodson, Matthew; Roberts, C Michael; Andrew, Sharon; Graham, Laura; Jones, Paul W; Yorke, Janelle
Abstract : We developed a chronic obstructive pulmonary disease (COPD) patient-reported experience measure (PREM-C9). 174 patients with COPD (86 [49%] with a confirmed diagnosis and 88 [51%] with a self-reported diagnosis of COPD) completed a 38-item list, COPD Assessment Test (CAT) and Hospital Anxiety and Depression Scale (HADS). Hierarchical and Rasch analysis produced a 9-item list (PREM-C9). It demonstrated fit to the Rasch model (χ² p=0.33) and correlated moderately with CAT (r=0.42), HAD-anxiety (r=0.30) and HAD-depression (r=0.41) (p<0.05). A substudy confirmed its ability to detect change prepulmonary and postpulmonary rehabilitation. The PREM-C9 is a simple, valid measure of experience of patients living with COPD, validated in this study population with mild to very severe disease; it may be a useful measure in research and clinical audits.